The Kinetics of Selective Biological Transport: III. Erythrocyte-Monosaccharide Transport Data - Miller, D. M. (1968)
The simplest biological transport system so far extensively investigated is that of monosaccharides in human erythrocytes. Despite its simplicity there is still considerable doubt and divergence of opinion concerning its mechanism. Some confusion may arise as a result of the comparison of diverse data obtained by different workers using a variety of experimental techniques. To minimize this problem, an attempt is made here to repeat, under standard conditions and with as much care as possible, five of the more definitive types of experiments previously performed on this system. It is hoped that the result of this effort is an internally consistent set of data with which the quantitative predictions of various proposed mechanisms may be compared as a primary criterion for their acceptability.